CSR Disclosure, Customer Loyalty, and Firm Values (Study at Mining Company Listed in Indonesia Stock Exchange) - Isnalita; I Made Narsa (Emerald Publishing Limited, 2017)
This study aimed to examine the association of Corporate Social Responsibility (CSR) disclosure and the firm valueson customer loyalty as a mediating variable. The samples of this study weresourced from the mining companies listed on the Indonesia Stock Exchange of 2008-2014. The secondary data used was obtained from the annual reports accessed through idx.co.id, and the sales reports based on the mining's sub-sectors accessed through bi.go.id. The variables of CSR disclosure were measured by usingscoresof weighting the item categories of CSR disclosure, namely: special items, core items, and additional items. Meanwhile, customer loyalty was measured by using market share, and the firm values were measured by Tobin's Q. The results proved that customer loyalty was the intervening influence of CSR disclosure and the firm values. This was the first study thatapplied different weighting to the category of disclosure items to calculate the scores of CSR disclosure through a statistical testing. Further research, then,can use the survey or focus group discussion (FGD) to determine the weighting method.